(untitled) (Biological Sciences - PJSIR, 1995)
The fixed oil from the seeds ofAchras zapata (N.O. Sapataceae) was extracted to the extent of 8.1%and studied for its physico-chemical properties and fatty acid composition.The oil containedpalmitic acid (20.5%), stearic acid (12.0%), oleic acid (58.5%) and linoleic acid (3.9%) as the major fatty acids.